Innovative Moments and Case Formulation: Finding Resources at the Onset of the Therapy - Magalhães, Carina; Pinheiro, Patrícia; Gonçalves, Miguel; Silva, Jéssica (Revista de Psicoterapia, 2022)
At the beginning of the therapeutic process, clients frequently feel immersed in their problems, and demoralized, with a negative perspective of different areas of their lives. The clients´ discourse is specially focused on difficulties and previous ineffective attempts to overcome their problems. Even though positive aspects of the clients’ life continue to exist, such as resources and strengths, they have little visibility in the clients’ speech and, consequently, in the therapist’s assessment and intervention planning. Moreover, most psychotherapy models emphasize a focus on the deficits of the clients, centered on the correction of difficulties as a way to achieve mental health. In this context, we highlight the importance of integrating resources and strengths of the clients’ life in case assessment, clinical formulation, and treatment planning. This information can be collected in the assessment phase, but in order to make it explicit the relevance of this information we created a protocol designed for this purpose (Feedback Initiated Narrative Development Protocol [FIND]). The first component of FIND invites clients to reflect on aspects beyond their problem like their personal strengths, significant values, positive autobiographical episodes, and useful strategies that have been adopted in the past. This interview was largely influenced by narrative therapy and innovative moments research, and it provides information regarding clients’ resources that may be useful to psychotherapists from different approaches. In this paper, we presented a clinical case formulation considering resources evaluated with the FIND protocol.